2013
DOI: 10.1177/0886260513505145
|View full text |Cite
|
Sign up to set email alerts
|

My Beliefs of My Peers’ Beliefs

Abstract: Dating violence in adolescent relationships is a growing social problem in the United States. A majority of adolescents have dated by the time they finish high school and these experiences have an impact on their relationship trajectories as adults. Although more and more prevention efforts are aimed at reducing teen dating violence and/or teaching adolescents about healthy relationships, very few of these efforts investigate discrepancies in descriptive and injunctive norms associated with adolescent dating. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…Research has shown the association between the perpetration of dating abuse and perceived peer violence (Reed, Silverman, Raj, Decker, & Miller, 2011), and also that perceptions of peer violence are generally closer to the respondents’ own behavior than to the self-reported behavior of the peer (Meldrum & Boman Iv, 2013; Perkins, Haines, & Rice, 2005). Also, because there is not temporally ordered, self-reported information about peer behaviors relative to the respondent youth’s ADA perpetration, these data do not support distinction of peer selection versus peer influence, or investigation of direct peer influences, along the lines of research examining male peers’ encouragement to perpetrate dating abuse (Capaldi et al, 2001), as a potential moderator of indirect influences (descriptive and injunctive norms; Hertzog & Rowley, 2014). This study did not specify the nature of the problem discussed with friends or the nature of friends’ responses, a critical area for investigation to guide prevention messages to friendship and peer groups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Research has shown the association between the perpetration of dating abuse and perceived peer violence (Reed, Silverman, Raj, Decker, & Miller, 2011), and also that perceptions of peer violence are generally closer to the respondents’ own behavior than to the self-reported behavior of the peer (Meldrum & Boman Iv, 2013; Perkins, Haines, & Rice, 2005). Also, because there is not temporally ordered, self-reported information about peer behaviors relative to the respondent youth’s ADA perpetration, these data do not support distinction of peer selection versus peer influence, or investigation of direct peer influences, along the lines of research examining male peers’ encouragement to perpetrate dating abuse (Capaldi et al, 2001), as a potential moderator of indirect influences (descriptive and injunctive norms; Hertzog & Rowley, 2014). This study did not specify the nature of the problem discussed with friends or the nature of friends’ responses, a critical area for investigation to guide prevention messages to friendship and peer groups.…”
Section: Discussionmentioning
confidence: 85%
“…The disparity in tolerance for hitting boyfriends more so than for hitting girlfriends may reflect the advantages of showcasing masculinity as Hertzog and Rowley (2014) suggest. Absent the showcasing restriction, the common tolerance of hitting boyfriends among girls who date is of grave concern and, further, is relevant to youth prevention programs that address relationships and communications within friendship groups.…”
Section: Discussionmentioning
confidence: 99%
“…stereotypes related to sports and intelligence) [ 45 , 51 , 63 , 64 , 68 , 72 , 73 , 78 , 87 , 95 , 96 , 110 , 118 , 125 ] or endorsement of gender inequitable norms [ 47 , 49 , 56 , 96 , 116 , 119 121 ]. Other measurement categories included attitudes about gender-based violence [ 55 , 58 , 67 , 108 , 119 ], evaluation of gender non-conforming behaviors [ 53 , 70 , 74 , 107 , 123 ], and perceptions of the “ideal” man or woman [ 46 , 69 , 81 ]. Due to the heterogeneity in the quantitative measures, it was not possible to compare the prevalence and range of gender attitudes across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Once again, peer risk factors may represent situational factors of the background-situational theory (Riggs & O'Leary, 1996), and mechanisms identified by the social learning theory may help understand this finding. Specifically, behaviors are learned through social interactions, and negative characteristics of the peer group can act as an unhealthy romantic relational model (Hertzog & Rowley, 2014). It has also been argued that CDA perpetrators seek and associated with others who have similar attitudes towards behaviors .…”
Section: Discussionmentioning
confidence: 99%